Search for pair production of first-generation leptoquarks in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (Elsevier B.V., 2009)
A search for pair production of first-generation leptoquarks (LQ) is performed with data collected by the do experiment in p (p) over bar collisions at root s = 1.96 TeV at the Fermilab Tevatron Collider. In a sample of data corresponding to similar to 1 fb(-1) the search has been performed on the final states with two electrons and two jets or one electron, two jets and missing transverse energy. We find our data consistent with standard model expectations. The results are combined with those found in a previous analysis of events with two jets and missing transverse energy to obtain scalar LQ mass limits. We set 95% C.L. lower limits on a scalar LQ mass of 299 GeV. 284 GeV and 216 GeV for beta = 1, beta = 0.5 and beta = 0.02 respectively, where beta is the LQ branching ratio in the eq channel. This improves the results obtained with a lower luminosity sample from Run II of the Tevatron. Lower limits on vector LQ masses with different couplings from 357 GeV to 464 GeV for beta = 0.5 are also set using this analysis. (C) 2009 Elsevier B.V. All rights reserved.